Bioavailability of Ruminally or Abomasally Infused L-carnitine in Holstein Heifers - K. Olagaray; C. Armendariz; A. Bellamine; S. Jacobs; E. Titgemeyer; B. Bradford (Kansas Agricultural Experiment Station Research Reports, 2016)
This study evaluated the relative bioavailability of carnitine delivered by different methods in dairy cattle. Four Holstein heifers were used in a split-plot design to compare ruminally or abomasally infused L-carnitine. The study included 2 main-plot periods, with infusion routes allocated in a crossover design. Within main-plot periods, each of 3 subplot periods consisted of 4-d infusions separated with 4-d rest periods. Subplot treatments were infusion of 1, 3, and 6 g L-carnitine daily. Doses were increased within a period to minimize carryover. Treatments were delivered in two 10-h infusions daily. Blood was collected before the start of infusions and on day 4 of each infusion to obtain baseline and treatment carnitine concentrations. There was a dose × route interaction (P<0.05) and route effect (P<0.01) for increases in plasma carnitine above baseline, with increases above baseline being greater across all dose levels when infused abomasally compared to ruminally. Results demonstrated superior bioavailability of carnitine when ruminal exposure was physically bypassed.
Keywords: L-carnitine; bioavailability; dairy cow